BEHAVIOUR TARGETED TRAINING: IMPROVING EMPLOYEE ENGAGEMENT IN A SMALL AND MEDIUM CANADIAN BUSINESS - Roberts, Lee (Digital Repository of Theses - SSBM Geneva, 2023)
Companies are struggling to keep operating costs under control. They are finding it more challenging to source supplies, especially since Covid-19, which has now been followed by an expected global recession, which has compounded the difficulties companies were already facing. In addition, many large businesses are increasingly outsourcing their manufacturing to cheaper countries, making it even more difficult for small and medium-sized companies to compete. With this quickly changing technology, supply issues, staffing challenges, and the global pandemic, businesses must explore better, more effective ways to do business. One of the most effective ways of doing that is through employee training. Training increases engagement and performance by enhancing skills and proficiency, as confirmed in this study. The other substantial part of the equation is the desire to engage in training and employee preference determined by personality and behaviour, which plays a role in our everyday interactions and engagement in tasks. Still, current research demonstrates a lack of focus and detail on structuring training based on personality preferences to increase engagement and performance. This research examines the three main training methods used in industry and aims to answer whether personality and behaviour traits make a difference in selecting training to increase employee engagement and performance.